Effects of Big Data Capacity on Sustainable Manufacturing and Circular Economy in Brazilian Industries - Klein, Luciana; Sano Guilhem, Ana Paula (Review of Business Management, 2024)
Purpose – The objective is to analyze the relationship between big data analytics (BDA) capability and the development of sustainable manufacturing and circular economy (CE) in Brazilian industries. Theoretical framework – The construction of BDA capability, according to the resource-based theory, is established through the implementation, integration and processing of big data resources. It is argued that BDA capability can contribute to the sustainable development of industries based on the collected data, as well as influencing the development of CE. Design/methodology/approach – The research was descriptive and quantitative, and was conducted using a survey of employees in Brazilian industries that use big data. The hypotheses were tested using structural equation modeling. Practical & social implications of research – BDA capability has a positive and significant relationship with sustainable manufacturing and CE. Sustainable manufacturing is a complementary mediator between BDA capability and CE. Originality/value – The study provides knowledge on the interaction between BDA and the development of sustainable and circular practices in Brazilian industries, providing incentives for changes in manufacturing companies that can successfully reduce social pressures due to resource scarcity, sustainable production and supply chain uncertainty. Keywords: Resource-based theory, big data capability, sustainable manufacturing, circular economy